ผลของคอปเปอร์ฟอสไฟด์ที่มีต่อการแข็งตัวและโครงสร้างจุลภาคของโลหะผสมอะลูมิเนียม-ซิลิคอนชนิดไฮเปอร์ยูเทกติก - อรจีรา ธนูเทพ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Mechanism and process parameters in the refinement of primary silicon are investigated. Cu3P is used as an additive for hyper-eutectic aluminum-silicon melt at silicon content of 15, 20, and 25 weight per cent and the amount of phosphorus addition from 0 to 0.1 weight per cent. Primary silicon size decreases and uniformly distributes with increasing amount of phosphorus addition. Chemical analysis of the specimen is performed to determine the retained phosphorus in the melt. Solidification sequence of the ternary alloys is also calculated using thermodynamic regular and sub-regular solution models of binary components. Phosphorus solubility in liquid melt is also calculated and agrees with the result from chemical analysis; it increases with temperature and decreases with silicon content. Thermodynamic analysis also indicates that there is a minimum limit of phosphorus addition to obtain the refinement effect. The amount of addition should be greater than the solubility limit to obtain the full effect of refinement. This is in agreement with the observed primary silicon size in cast specimen.